2017
DOI: 10.1097/igc.0000000000001081
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Aurora Kinase A Synergistically Enhances Cytotoxicity in Ovarian Clear Cell Carcinoma Cell Lines Induced by Cisplatin

Abstract: Aurora-A is a promising biomarker that is predictive of patient outcomes and a potential target for OCCC. The results suggested that chemotherapy, including ENMD-2076 in combination with cisplatin, is a potential treatment modality for patients with OCCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…In addition, AURKA expression predicts platinum resistance in patients with high-grade serous ovarian carcinoma (Mignogna et al, 2016). Inhibiting AURKA by inhibitor ENMD-2076 enhances the cytotoxic effect of cisplatin in ovarian cancer (Chiba et al, 2017;Diamond et al, 2018). Our result is consistent with the effect of AURKA inhibitor on cisplatin therapy reported before (Chiba et al, 2017) and makes us more confident about the potential of emodin to use as an AURKA inhibitor in ovarian cancer therapy.…”
Section: Emodin On Aurka Activity and Ovarian Cancer Cisplatin Treatmentsupporting
confidence: 87%
“…In addition, AURKA expression predicts platinum resistance in patients with high-grade serous ovarian carcinoma (Mignogna et al, 2016). Inhibiting AURKA by inhibitor ENMD-2076 enhances the cytotoxic effect of cisplatin in ovarian cancer (Chiba et al, 2017;Diamond et al, 2018). Our result is consistent with the effect of AURKA inhibitor on cisplatin therapy reported before (Chiba et al, 2017) and makes us more confident about the potential of emodin to use as an AURKA inhibitor in ovarian cancer therapy.…”
Section: Emodin On Aurka Activity and Ovarian Cancer Cisplatin Treatmentsupporting
confidence: 87%
“…Aurora-A is an oncogene in mammary epithelium and gland (11, 12), whereas it functions as a tumor suppressor in neural stem cells (13), so Aurora-A functions differ depending on the cell type. Aurora-A has been reported in the gynecologic cancers, such as breast cancer (18), ovarian cancer (20, 24), and EC (22), but the underlying molecular mechanism of Aurora-A-mediated chemoresistance in EC is unclear. In the present study, we revealed that both of mRNA and protein up-regulation of Aurora-A frequently occur in EC and contribute to a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidences have shown that overexpression of Aurora-A is associated with chemoresistance (14–19). Recent reports showed that Aurora-A is correlated with the resistance to carboplatin/Cisplatin and indicates a poor prognosis (20, 21). Aurora-A has been noted to be a novel therapeutic target for the gynecological malignancies, however, only a few reports have described a role for Aurora-A in EC.…”
Section: Introductionmentioning
confidence: 99%
“…This overexpression is also correlated with decreased survival in women with early stage disease [20,21]. In advanced OCCC, increased Aurora-A expression was associated with worse overall survival [22]. A recent study had shown that overexpression of Aurora Kinase A was significantly associated with chemoresistance in OCCC, suggesting that targeted at Aurora Kinase might provide a promising therapeutic option [23].…”
Section: Introductionmentioning
confidence: 99%